Economic Growth and Kaldor’s Growth Laws: Evidence From Malaysia - Hamri, Tuah (Universiti Malaysia Sarawak, (UNIMAS), 2001)
In most previous literature on growth and development, two types of empirical study have been conducted. The first type involves country regression analysis and the type focuses on growth accounting exercises. However, neither of these two approaches picks out any one particular sector, as the driving force behind the growth of any country will be linked to the growth of its most dynamic sector. It was always the connection of Nicholas Kaldor that the manufacturing sector is the engine of growth and that conventional studies of growth are far too aggregative in their approach.